A method for man hour optimisation and workforce allocation problem with discrete and non-numerical constraints in large-scale one-of-a-kind production. Issue 3 (1st February 2016) - Mei, Ying; Zeng, Zhigang; Feng, Ding; Tu, Yiliu (Paul)
Abstract : In one-of-a-kind production (OKP), how to coordinate workforce allocations to obtain reasonable man-hour has the practical significance. However, plenty of variables and complicated operation relationships are involved, which implies the man-hour optimisation in OKP belongs to a constrained mixed discrete optimisation problem. In this article, to deal with the man-hour optimisation in large-scale OKP which often refers to complex production, e.g. shipbuilding, we introduce a top-down refinement method to specialise the product design and production decomposition in OKP, which also indicates the operation relationships of the interim product production processes. Consequently, we suggest three basic task structures which are with wide adaptability in OKP industry: tandem structure, parallel structure and double-level-nested parallel structure. Meanwhile, for the double-level-nested parallel structure, a method based on matrix real-coded genetic algorithm and dynamic programming is presented to solve the man-hour optimisation and labour force allocation problem. Through the case studies, including an industrial implementation in the shipbuilding interim product (i.e. a hull block) production, our optimisation method demonstrates significant potential to improve the production efficiency.